IDENTIFIKASI KETEPATAN PENGGUNAAN OBAT ANTI EPILEPSI PADA PASIEN EPILEPSI RAWAT JALAN DI RSUD DR. MOEWARDI PERIODE JANUARI - JUNI 2024: THE CORRECT IDENTIFICATION OF A CURE FOR EPILEPSY IN AN OUTPATIENT EPILEPTIC WARD AT DR. MOEWARIN JANUARY - JUNE 2024 - Fitriani, Suci; Sakti Pambudi, Risma; Khusna, Khotimatul (JFL : Jurnal Farmasi Lampung, 2025)
Epilepsy is a chronic disorder as a result of brain dysfunction that is characterized by repeated seizures. A major therapy for epilepsy was the administration of anti-epileptic drugs (AEDs). AED identification is important in epileptic patients because anti-epileptic drugs are used over a long period of time. The purpose of this study is to understand the precise rate of use of antiepileptic drugs in outpatient epilepsy at Dr. Moewarin January-June 2024. The study USES descriptive methods with data retrieval retrospectively. The instruments used in this study are the patient's medical records. Identify the correct use of drugs in this study using Doxide (meetings of the Indonesian nerve specialist) 2019 and hospital formulations 2024 -2025 with precise criteria of indicative, precise patients, precise drugs and precise doses. Research indicates that the use of anti-epileptic drugs in an outpatient setting at Dr. Moewarin in the January-June 2024 period is the exact rate 100%, exact patients 100%, exact drugs 100%, and exact dosage 94%. Keywords: Epilepsy, precise indications, proper patients, right medication, right dosage.